Case Report: Incidental late-onset Pompe disease diagnosis in a man with no clinical and instrumental evidence of neuromuscular dysfunction - Sciacco, Monica; Lucchiari, Sabrina; Bertolasi, Letizia; Comi, Giacomo Pietro; Corti, Stefania; Ronchi, Dario (Frontiers in Genetics, 2025)
Glycogen storage disease II or Pompe disease (PD), is a rare autosomal recessive disorder due to biallelic pathogenic variants in GAA, resulting in the enzymatic deficiency of alpha-1,4-glucosidase. Two clinical forms are recognized, namely, early onset (EOPD) and late-onset (LOPD). We present the case of an asymptomatic 33-year-old man who underwent a genetic screening for autosomal recessive disorders (parental prenatal counselling) and was found to carry the homozygous pathogenic GAA substitution NM_000152.5(GAA):c.-32-13T>G (IVS1). Neurological examination, serum CK levels, electromyography, muscle MRI, respiratory and cardiac screening were reported normal. We investigated the effects of the variant at transcript and protein levels in available tissues from the proband and his parents. The IVS1-32-13T>G variant (dbSNP: rs386834236, Clin Var ID: 4,027) occurs in 90% of Caucasian LOPD patients and is associated with a broad range of symptom onset. About 50 subjects have been reported harboring this variant in homozygosis and most of them are asymptomatic, although a subset develops symptoms with time. Residual levels of alpha-1,4-glucosidase activity and protein content do not seem to reflect clinical severity in homozygous IVS1 LOPD patients.